23. HYPONATREMIA IN PATIENTS HOSPITALIZED IN THE ENDOCRINOLOGY DEPARTMENT: PREVALENCE AND ASSOCIATED FACTORS (Vietnam Journal of Community Medicine, 2024)
Objective: Hyponatremia is a common electrolyte disorder in hospital inpatients and the community. Hyponatremia is associated with adverse outcomes such as increased morbidity, falls, prolonged hospitalization, and mortality. The study aimed to estimate the prevalence and associated factors of hyponatremia in patients admitted to the endocrinology department.Subject and method: A retrospective observational study on hyponatremia patients admitted to the endocrinology department at Thong Nhat Hospital for 12 months. Hyponatremia is defined as the first recorded plasma sodium concentration on admission below 135 mmol/L. The clinical features, underlying causes, and main outcomes of hyponatremia patients were documented for analysis.Results: During the indicated period, 410 patients with hyponatremia were hospitalized, including 163 men and 247 women with a mean age of 67 ± 15 years. The prevalence of admission hyponatremia was 25.1%. The most common symptoms of hyponatremia were fatigue, followed by nausea and dizziness. The prevalence of hypertonic, isotonic, and hypotonic hyponatremia was 46.8%, 4.2%, and 49%, respectively. When compared with milder hyponatremia patients, patients with more severe hyponatremia were associated with significant increases in hospitalization from the emergency room, symptoms of vomiting, and mental disturbances. The severity of hypotonic hyponatremia was classified as mild (52.2%), moderate (15.9%), severe (11.5%), and critical (20.4%). The common causes of hypotonic hyponatremia were thiazide diuretics, volume depletion, SIADH, and endocrine diseases. The median length of hospital stay was 9 days with an inpatient mortality rate of 1%. There were no significant differences in main outcomes between hypotonic hyponatremia severity groups.Conclusion: Hyponatremia was highly prevalent among the patients admitted to the endocrinology department. It was estimated that one in four patients who were admitted to the endocrine unit had hyponatremia, among these cases, true hyponatremia accounted for nearly half. No statistically significant association was found between hyponatremia severity and inpatient mortality.
Keywords: hyponatremia; hospitalization; endocrinology